The effect of low volume high-intensity interval training on metabolic and cardiorespiratory outcomes in patients with type 2 diabetes mellitus: A systematic review and meta-analysis - Peng, Yang; Ou, Yiran; Wang, Ke; Wang, Zhenghao; Zheng, Xiaofeng (Frontiers in Endocrinology, 2023)
Abstract Aims The present systematic review and meta-analysis of randomized controlled trials (RCTs) was conducted to investigate the effect of low volume high-intensity interval training (LVHIIT) on the metabolic and cardiorespiratory outcomes in patients with type 2 diabetes mellitus (T2DM). Methods Relevant articles were sourced from PubMed, EBSCO, Web of Science, Embase, and the Cochrane Library from inception to October 2022. The study search strategy and all other processes were implemented in accordance with the PRISMA statement. Results Five randomized controlled trials that satisfied the inclusion criteria were included in this meta-analysis. The LVHIIT group had significantly lower fasting blood glucose levels (RR= -1.21; 95% CI= -2.02— -0.40, p = 0.0032) and HbA1c levels (RR= -0.65; 95% CI= -1.06— -0.23, p = 0.002) and higher levels of insulin resistance indicator HOMA-IR (RR= -1.34; 95% CI = -2.59— -0.10, p = 0.03) than the control group. Moreover, our results show that LVHIIT can reduce body mass (RR = -0.94, 95% CI = -1.37— -0.51, p<0.0001) and body mass index (RR = -0.31, 95% CI = -0.47— -0.16, p<0.0001). LVHIIT had a better therapeutic effect on blood lipid metabolism, such as total cholesterol, high-density lipoprotein, low-density lipoprotein and triglycerides. However, the change in fasting insulin levels was not statistically significant (RR= -1.43; 95% CI = -3.46— 0.60, p =0.17). Furthermore, LVHIIT reduced the systolic blood pressure (RR =-4.01, 95% CI = -4.82 – -3.21, p<0.0001) and improved peak oxygen uptake (VO2peak) compared to the control group (RR= 5.45; 95% CI = 1.38 – 9.52, p =0.009). Conclusion After a certain period of LVHIIT, glycaemic control, insulin resistance, body weight, lipid profile and cardiorespiratory outcomes were significantly improved in T2DM patients.